Serat Wulangreh Pupuh Kinanthi untuk Pembelajaran Budi Pekerti Siswa SMP - Lestyowati, Sri; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2025)
Moral education in schools is an essential part of character development rooted in local cultural values, particularly Javanese culture, which upholds the principle of “Wong Jawa Saé Ilang Jawane” (Javanese people should not lose their Javanese identity). Serat Wulangreh, written by Sri Susuhunan Pakubuwana IV—especially the Pupuh Kinanthi section—contains moral teachings that are highly relevant for junior high school students. This study aims to explain how moral education based on Wulangreh Pupuh Kinanthi is implemented for students at SMP. This research adopts a qualitative descriptive approach with a case study method. Data collection techniques include classroom observations, in-depth interviews with Javanese language teachers and students, and documentation of texts and teaching materials. The findings reveal that Pupuh Kinanthi conveys moral values such as respect for parents, humility, patience, and the importance of knowledge. These values are taught through appropriate methods such as class discussions, verse-by-verse interpretation, and personal reflection. This learning approach has been proven to increase students' awareness of the importance of good attitudes and behaviors in daily life, despite some challenges such as limited instructional time and low student interest in classical literature. This study recommends the use of local texts as effective media for character education that align with cultural contexts and contemporary needs.